2011
DOI: 10.4103/0189-6725.91676
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in paediatric age group: Correlation between preoperative inflammatory markers and postoperative histological diagnosis

Abstract: CRP and WBCC are simple tests that can provide a significant role supporting the clinical diagnosis of acute appendicitis in the paediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
13
1
1
Order By: Relevance
“…It has been reported that the WBCC was increased in children with AA in comparison with those with negative appendicectomies. [14,18] However, other studies did not find differences in the WBCC between the two groups. Stefanutti et al, [12] in a study of 100 patients who underwent appendicectomy, found similar results in children with simple AA and those with negative operative findings.…”
Section: Researchmentioning
confidence: 73%
See 3 more Smart Citations
“…It has been reported that the WBCC was increased in children with AA in comparison with those with negative appendicectomies. [14,18] However, other studies did not find differences in the WBCC between the two groups. Stefanutti et al, [12] in a study of 100 patients who underwent appendicectomy, found similar results in children with simple AA and those with negative operative findings.…”
Section: Researchmentioning
confidence: 73%
“…[20,25,26] However, other researchers have found similar proportions of boys and girls, [10][11][12]14,18,19] and even a predominance of girls over boys. [15] It is interesting to point out that patients with negative appendicectomies were mainly girls, [13] even when the three patients in this group who had a gynaecological disease are excluded.…”
Section: Researchmentioning
confidence: 86%
See 2 more Smart Citations
“…Sengupta et al [17] even suggest that patients with lower abdominal pain with a normal WBC and CRP can be sent home. Besides adults it can also provide a significant role supporting the clinical diagnosis of acute appendicitis in the pediatric age group [18][19][20]. While these markers have shown early promise, the power of the studies is limited due to the small sample size.…”
Section: Introductionmentioning
confidence: 99%